DIRECTORS' LEGAL RESPONSIBILITIES: AN ANALYSIS OF THE COMPANIES ACT 2006'S INFLUENCE ON UK CORPORATE GOVERNANCE - Boateng , Kwame Ayisi; Mensah, Esther Akua (Ayden International Journal of Law, Political Science, and Administration, 2024)
The United Kingdom's Company Law Steering Group (CLRSG) initiated a review of the UK company law from 1998 to 2001, resulting in a recommendation to codify directors' duties into statute, which led to the introduction of the Companies Act 2006 (2006 Act). Chapter 2 of Part 10 of the 2006 Act codified the general duties of directors to their respective companies. These statutory duties encompass obligations to act within their powers, promote the success of the company, exercise independent judgment, exercise reasonable care, skill, and diligence, avoid conflicts of interest, decline benefits from third parties, and declare interests in proposed transactions or arrangements. These duties are owed to the company as a whole, rather than to individual shareholders. However, in exceptional circumstances, such duties may be owed to individual shareholders. This article explores the intricacies of directors' duties as codified in the 2006 Act, the exceptions where shareholders may have recourse, and the implications for corporate governance